Yield potential of garden pea varieties at varied harvesting dates - Haque, SR; Akter, N; Khan, MAH; Kabir, K; Islam, MM (Bangladesh Agronomy Journal, 2015)
A field experiment was carried out at the experimental field of Department of Genetics and Plant Breeding of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur during November 2008 through April 2009 to find out the performance of different pea varieties at different harvesting time. The treatments consisted of two factors, which were four harvesting times (70, 80, 90 and 100 days after sowing) and six varieties of garden pea (IPSA Motor shuti-1, IPSA Motor shuti-2, IPSA Motor shuti-3, BARI Motor shuti-1, BARI Motor shuti-3 and Local white). The experiment was laid out in a randomized complete block design with three replications. The maximum pod yield (11.42 t ha-1) was obtained from BARI Motor shuti-1 harvesting at 80 days after sowing which was statistically similar to IPSA Motor shuti-2 harvesting at 80 days after sowing and Local white at same harvesting date and superior to the rest of the treatment combination. The lowest pod yield (5.25 t ha-1) was produced by BARI Motor shuti-1 harvesting at 70 days after sowing. Bangladesh Agron. J. 2014, 17(2): 21-28